TOTAL ABNORMAL PULMONARY VEIN DRAINAGE - Mamatov Mukhammadzhon Akhmadovich (Galaxy International Interdisciplinary Research Journal, 2022)
To the article " Total anomalous pulmonary venous drainage". In this scientific article, the authors describe a literature review of total anomalous pulmonary venous drainage (TAPD). In this regard, the study of the clinical course and diagnostic methods of TADLV is relevant, which makes it possible to timely detect the defect, rationally plan the examination and choose the optimal method of correction. The definitions, frequency of occurrence, causes of the defect and diagnostic methods are described, including echocardiography, multislice computed tomography with contrast and catheterization of the heart cavities with angiocardiography. Various types of surgery are described for various variants of TADLV . Depending on the level of confluence of the pulmonary veins and the location of the ASD, patients were divided into 4 groups: supracardial , cardiac , infracardial and displaced . Literature review describes the complications of the defect and the results of the operation.